2023
DOI: 10.1097/hep.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Predicting futility of upfront surgery in perihilar cholangiocarcinoma: Machine learning analytics model to optimize treatment allocation

Francesca Ratti,
Rebecca Marino,
Pim B. Olthof
et al.

Abstract: Background: Whilst resection remains the only curative option for perihilar cholangiocarcinoma (PHC), it is well known that such surgery is associated with a high risk of morbidity and mortality. Nevertheless, beyond facing life-threatening complications, patients may also develop early disease recurrence, defining a “futile” outcome in PHC surgery. The aim of this study is to predict the high-risk category (futile group) where surgical benefits are reversed and alternative treatments may be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In our study, bilirubin levels within a week before receiving immunotherapy were related to the total survival time of the patients (mOS: 1508 vs. 263 days), with higher levels indicating a worse prognosis. Bilirubin levels affect patients with cholangiocarcinoma's prognosis in several ways: Patients with hilar cholangiocarcinoma with higher bilirubin levels at diagnosis may not benefit from surgery (34); The albumin bilirubin (ALBI) grade, which combines bilirubin and albumin levels, is an independent prognostic factor for OS and PFS in intrahepatic cholangiocarcinoma (35,36). The analysis of FIB-4, SII, NLR, PLR, and PNI showed that FIB-4 is an independent risk factor for OS in patients with cholangiocarcinoma undergoing immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, bilirubin levels within a week before receiving immunotherapy were related to the total survival time of the patients (mOS: 1508 vs. 263 days), with higher levels indicating a worse prognosis. Bilirubin levels affect patients with cholangiocarcinoma's prognosis in several ways: Patients with hilar cholangiocarcinoma with higher bilirubin levels at diagnosis may not benefit from surgery (34); The albumin bilirubin (ALBI) grade, which combines bilirubin and albumin levels, is an independent prognostic factor for OS and PFS in intrahepatic cholangiocarcinoma (35,36). The analysis of FIB-4, SII, NLR, PLR, and PNI showed that FIB-4 is an independent risk factor for OS in patients with cholangiocarcinoma undergoing immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To the editor, We read with great interest the paper by Dr. Ratti and colleagues. [1] The study included 2271 patients with perihilar cholangiocarcinoma (PHC) who underwent surgical resection at 27 institutions and developed a preoperative risk score for predicting futile outcomes following surgery for PHC. This risk score demonstrated simplicity and accuracy in predicting the risk of futile outcome and provided reliable guidance in avoiding unnecessary surgery for PHC patients.…”
mentioning
confidence: 99%
“…We read with great interest the paper by Dr. Ratti and colleagues 1 . The study included 2271 patients with perihilar cholangiocarcinoma (PHC) who underwent surgical resection at 27 institutions and developed a preoperative risk score for predicting futile outcomes following surgery for PHC.…”
mentioning
confidence: 99%
“…Although these factors often are evaluated together in a clinical setting, they have most commonly been separated in outcomes/risk studies. The combination of poor outcomes both cancer-specific and from a complication standpoint is a unique and important contribution that Ratti et al 8 have defined as surgical “futility.”…”
mentioning
confidence: 99%